G protein mutations that alter the pheromone response in Saccharomyces cerevisiae. - Stone, D E (1990)
The GPA1 gene of Saccharomyces cerevisiae encodes a G alpha protein that couples the membrane-bound pheromone receptors to downstream elements in the mating response pathway. We have isolated seven mutant alleles of GPA1 that confer pheromone resistance: G50D (a glycine-to-aspartate change at position 50), G322E, G322R, E355K, E364K, G470D, and an E364K-G470D double mutant. All of the mutations lie within large regions that are highly conserved between Gpa1 and four other G alpha proteins; four of the changes are located in domains with proposed functions. On the basis of a gentic analysis, the pheromone-unresponsive GPA1 alleles can be divided into two classes: those that encode constitutively activated proteins and those that encode proteins unable to respond to the upstream signal. Our results support the hypothesis that the activated form of Gpa1 stimulates adaptation to pheromone.